An alternative method in fixation of tibial transverse fractures by intramedullar nailing: Biomechanical and histopathologic investigation - Varis, Onur; Aksakal, Bunyamin; Say, Yakup; Kom, Mustafa; Yilmaz, Erhan (Paradigm Publishing Services-de Gruyter Brill Sp Zoo, 2013)
A new method was used in fixation of tibial bone fractures. Intramadular nailing (IMN) has been used into mid-diaphysis on left tibias of New Zeland rabbits (n = 5) via an in vivo work. To enable fixation of fracture, without causing too much screw damage on bone and avoiding malunion, nano-and micro-scale hydroxyapatite (HA) was coated at two ends (25 mm in length) of intramadular nails before implantation. After six weeks of survival period and sacrifizing, biomechanical tests and histopathologic examinations were executed. Such experiments have revealed that good stabilization and hence better fracture union for both treated IMN groups (NHA and MHA) over the standard IMN'. Pull-out tests showed the tensile strengths obtained to be significantly higher for the nano (NHA) and micro scale-MHA coated IMN compared to the uncoated standard IM nailing.
Keywords: bone fractures; intramedular nails; coating; fixation; biomechanics